2015
DOI: 10.2134/cftm2014.0085
|View full text |Cite
|
Sign up to set email alerts
|

Updating North Carolina Corn Yields and Nitrogen Recommendations to Match Current Production Practices and New Hybrids

Abstract: Corn (Zea mays L.) nitrogen (N) rate trials conducted in North Carolina over a recent 10‐year time frame (2001–2011) were reviewed to potentially adjust yield goals (realistic yield expectations [RYE]) and their associated N rate recommendations in the North Carolina RYE database. The analyzed trial data provided evidence that corn yields increased by 15, 18, and 31% in the Coastal Plain, Piedmont, and Mountain regions, respectively. To reflect these increases, realistic yield expectations in the database were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Arrows indicate estimated economic optimum N rates. and North Carolina [Rajkovich et al, 2015;1.43 × 10 -2 to 1.79 × 10 -2 kg N (kg grain) -1 or 0.8-1.0 lb N bu -1 ].…”
Section: Internal Nitrogen Requirementmentioning
confidence: 99%
“…Arrows indicate estimated economic optimum N rates. and North Carolina [Rajkovich et al, 2015;1.43 × 10 -2 to 1.79 × 10 -2 kg N (kg grain) -1 or 0.8-1.0 lb N bu -1 ].…”
Section: Internal Nitrogen Requirementmentioning
confidence: 99%
“…Therefore, these results suggest that private farms had more enriched surface soil than on research stations. Furthermore, historical calibrations of N fertilizer requirement for corn in North Carolina, which would have been conducted primarily on research stations (Rajkovich et al, 2015), may not have captured the full range of soil conditions found on private farms. Irrespective of location, these results suggest there can be a large quantity of mineralizable N present in surface soil to provide a significant fraction of N to a cropping system.…”
Section: Net Nitrogen Mineralizationmentioning
confidence: 99%
“…7C). This 121 kg N ha -1 discrepancy reflects a decision made by the North Carolina Nutrient Management Group in setting the RYE rate for Comus (historically high-yielding floodplain soil) higher than the LP average optimum N rate of around 80 kg N ha -1 (Rajkovich et al, 2015). The yield equation for x < 67 kg N ha -1 was y = 9547 + 101.9x (r 2 = 0.64 and p < 0.0001) and for x > 67 kg N ha -1 was y = 16,337 kg ha -1 .…”
Section: Regionmentioning
confidence: 99%